When I read, I breathe (Palíndromo, 2021)
This article presents the production of the artist Roni Horn, focusing on the routes and contagions between contemporary art and practices of reading and writing. Avoiding a hierarchical or categorizing approach, the following subjects are treated: texts as margins and / or crossings in her work; titles and footnotes that constitute artistic work inseparably connected with photographic images (You are the weather, Still Water and Another water); and works that give sculptural and / or graphic body to her reading of the oeuvres of Simone Weill, Franz Kafka, Clarice Lispector and Emily Dickinson. Based on the relationship between drawing and breathing, defended by the artist, as a vital, corporal, continuous and anchored in the present practice, it is proposed to extend this conception to Horn's writing-reading.
Keywords: Roni Horn; contemporary art; breathing; reading and writing practices